Study of aerofoil characteristics near/round stall points [electronic resource] - Abu Hassan Moksen, 1989-; Wan Zaidi Wan Omar, supervisor (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Aeronautik)) - Universiti Teknologi Malaysia, 2012